Penerepan Metode Waterfall Dalam Sistem Informasi Manufaktur Pada Usaha Fitria Konveksi - Awang Andhyka; Rizky Aditya Nugroho; Vivi Izzah Nur Kholifah (Institut Teknologi Adhi Tama Surabaya, 2022)
Manufacturing is a Latin word which, if interpreted broadly, is the process of converting raw materials into products. The process of converting raw materials into finished materials starting from the process of selecting raw materials to the stages of the product manufacturing process which will produce a product that goes through several stages of the production process. In a more modern context, manufacturing involves the manufacture of products from raw materials through various processes, machines, and operations, following a well-organized plan for each required activity. All objects that we encounter are made through various processes called fabrication (manufacturing). The purpose of this research is to make it easier to manage books such as product stock, raw material stock, production and orders that were originally done on worksheets, switch to easy-to-use programs. This research uses the waterfall method. The results of this study are to produce an information system that facilitates the manufacturing process starting from the process of raw materials, production to products ordered by customers.